(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Poor nutrition can lead to malnutrition due to micronutrient deficiencies, posing serious public health issues. Promoting traditional foods is one approach, with a sustainable impact on addressing micronutrient deficiencies, being explored in the Democratic Republic of Congo. This study aimed to determine and compare the mineral profile of three types of traditional bicarbonate produced from the leaves and spadices of the oil palm (Elaeis guineensis), the leaves of the water hyacinth (Eicchornia crassipes), and the peels of plantains (Musa x paradisiaca). Samples were analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES). Data analysis revealed that these three types of traditional bicarbonate have notable mineral contents, with varying levels of calcium, sulfur, magnesium, iron, zinc, manganese, and copper. The noteworthy concentrations of these nutritionally relevant minerals suggest that these three types of traditional bicarbonate could serve as good sources of essential minerals for preventing malnutrition due to micronutrient deficiencies and potentially helping prevent non-communicable chronic diseases. Int. J. Agril. Res. Innov. Tech. 14(2): 38-43, December 2024